Transabdominal preperitoneal repair for bilateral inguinal hernias: A single center experience - Haksal, Mustafa Celalettin; Okkabaz, Nuri; Civil, Osman; Kement, Metin; Öncel, Mustafa (My University, 2018)
Aim: To evaluate outcomes of transabdominal preperitoneal repair in patients with bilateral inguinal hernias. Methods: Sociodemographic data, and data about disease and operation with postoperative data of all patients with bilateral inguinal hernias, who were treated by transabdominal preperitoneal repair were prospectively collected. Patients were followed-up for recurrence and chronic pain in the long-term. Results: A total of 70 (67 [95.7%] males, mean age was 53.4±13.6 years) cases were included. Total 138 hernias (mostly Nyhus type 3 [n=116; 84.1%]) were repaired in 70 cases. Unilateral inguinal hernia was diagnosed in two cases during the operation. Mean operation time was 80.6±26.5 minutes. Inferior epigastric vein was injured in 2 (1.4%) cases. Parenteral analgesics were required in only 10 (14.3%) patients. Patients were discharged 1.21±0.67 days after the operation, and only 9 (12.8%) cases were hospitalized more than one day. Patients returned work or normal activity 10.5±4.7 days after the surgery. The mean follow-up period was 25.9±19.4 months. Symptomatic recurrence was observed in 2 (1.4%) patients. Six (8.7%) cases had chronic pain. Conclusion: Transabdominal preperitoneal repair may be an alternative approach in treatment of bilateral inguinal hernias.

Amaç: Bilateral kasık fıtığı olan hastalarda transabdominal preperitoneal tamir sonuçlarını irdelemek. Yöntemler: Transabdominal preperitoneal yöntemle bilateral kasık fıtığı tamiri uygulanan tüm hastalarda prospektif olarak sosyodemografik veriler, hastalık ve operasyona ait veriler ile postoperative veriler değerlendirildi. Uzun dönemde hastalar kronik ağrı ve nüks açısından takip edildi. Bulgular: Toplam 70 hasta (67 [95.7%] erkek, ortalama yaş 53.4±13.6) çalışmaya dahil edildi. İki hastada ameliyat esnasında tek taraflı fıtık saptandığından toplam 138 fıtık (Nyhus tip 3 [n=116; %84.1]) tamiri yapıldı. Ortalama operasyon süresi 80.6±26.5 dakikaydı. İki hastada inferior epigastrik ven yaralanması görüldü. Sadece 10 (%14.3) hastada parenteral analjezik ihtiyacı gelişti. Ortalama hastanede kalış süresi 1.21±0.67 gün olup sadece 9 (%12.8) hastada bir günden fazla yatış gerekti. İş veya normal aktivitelere dönüş süresi 10.5±4.7 gündü. Hastalar ortalama 25.9±19.4 ay takip edildi. Semptomatik nüks 2 (%1.4) hastada gelişti. Kronik ağrı ise 6 (%8.7) hastada saptandı. Sonuç: Bilateral kasık fıtıklarında transabdominal preperitoneal tamir bir alternatif olarak düşünülebilir
Bilateral kasık fıtıklarında transabdominal preperitoneal onarım: Tek merkez deneyimi
Keywords: Inguinal Hernia; Hernia Repair; Recurrence; Laparoscopy; Kasık Fıtığı; Fıtık Tamiri; Nüks; Laparoskopi